Principle and application of in-situ monitoring system for ground displacement induced by shield tunnelling. (June 2021) - Jiang, Hua; Cheng, Jinguo; Zhang, Jinxun; Zhang, Jingling; Su, Yiran; Zheng, Yaofu
Highlights: The method of real-time ground displacement monitoring was proposed. On-site observation stations for ground displacement were established. Field tests verified the accuracy and applicability of the monitoring system. Abstract: The ground displacements with complicated distribution induced by metro shield crossing and overlapping construction can significantly influence the stability of surrounding tunnels and structures, which really need to be monitored in practice systematically and exactly. In the present work, a high-accuracy monitoring system at the observation station was developed to precisely and real-timely monitor ground displacements in different depths. The present system combines the static level gauge with a single-point extensometer by platform anchorage, ensuring the real-time displacement monitoring automatically realized with high precision, high frequency and low disturbance. Additionally, a method of spatial coordinate transformation for different subsurface displacements is proposed to obtain the displacement values at the same borehole. The multiple regression analysis method is applied to eliminate the influence of actual unstable construction factors on the monitoring results, and it determines the displacement corrections modified by main factors including the selected monitoring point coordinates and tunnelling parameters. Two case studies in Beijing Subway Line 14 and New Airport Express have shown that the present monitoring method is feasible and suitable to describe the ground displacements under different geological conditions.